Introduction to managerial accounting - Brewer, Peter C. (McGraw-Hill, 2007)
Introduction to Managerial Accounting, 3/e by Brewer/Garrison/Noreen is based on the market-leading text, Managerial Accounting, by Garrison, Noreen and Brewer. However, this is not simply a briefer book with chapters removed; B/G/N has been rethought and retooled to meet the needs of the market. .